ROLE OF MALONDIALDEHYDE IN THE SERUM OF RHEUMATOID ARTHRITIS AND OSTEOARTHRITIS - Vyas, Shalini; Sharma, Hemlata; RK, Vyas (Journal of Postgraduate Medical Institute, 2016)
Objective: To measure malondialdehyde in order to determine oxidative stress in rheumatoid arthritis and osteoarthritis subjects and comparing them with healthy individuals. Methodology Malondialdehyde estimation were done by using the UV-VIS spectrophotometer in the department of biochemistry SP medical college, Bikaner. Thiobarbituric acid assay method was used to estimate Malondial-dehyde . Results: A statistically significant elevation of MDA level in serum of rheuma-toid arthritis (RA) and osteoarthritis (OA) subjects was seen (p<0.0001). The serum MDA level was also significantly increased in the subjects than in the controls. The serum MDA level was also significantly increased in the subjects than in the controls. Conclusion: Oxidative stress is due to increased free radical production which is the main mechanism in the pathogenesis of of RA and OA.